Current evidence for the management of rheumatoid arthritis with biological disease-modifying antirheumatic drugs: a systematic literature review informing the EULAR recommendations for the management of RA. Issue 6 (6th May 2010) - Nam, J L; Winthrop, K L; van Vollenhoven, R F; Pavelka, K; Valesini, G; Hensor, E M A; Worthy, G; Landewé, R; Smolen, J S; Emery, P; Buch, M H
Abstract : Objectives: To review the evidence for the efficacy and safety of biological agents in patients with rheumatoid arthritis (RA) to provide data to develop treatment recommendations by the European League Against Rheumatism (EULAR) Task Force. Methods: Medline, Embase and Cochrane databases were searched for relevant articles on infliximab (IFX), etanercept (ETN), adalimumab (ADA), certolizumab-pegol (CZP), golimumab (GLM), anakinra (ANA), abatacept (ABT), rituximab (RTX) and tocilizumab (TCZ) published between 1962 and February 2009; published abstracts from the 2007–2008 American College of Rheumatology (ACR) and EULAR conference were obtained. Results: 87 articles and 40 abstracts were identified. In methotrexate (MTX) naïve patients, biological therapy with IFX, ETN, ADA, GLM or ABT has been shown to improve clinical outcomes (level of evidence 1B). In MTX/other synthetic disease-modifying antirheumatic drug (DMARD) failures all nine biological agents confer benefit (1B), with lower efficacy noted for ANA. RTX, ABT, TCZ and GLM demonstrate efficacy in tumour necrosis factor inhibitor (TNFi) failures (1B). Less evidence exists for switching between IFX, ETN and ADA (3B). Biological and MTX combination therapy is more efficacious than a biological agent alone (1B). A safety review shows no increased malignancy risk compared with conventional DMARDs (3B). TNFi are generally associated with an increased risk of serious bacterial infection, particularly within the first 6 months of treatment initiation; increased tuberculosis (TB) rates with TNFi are highest with the monoclonal antibodies (3B). Conclusions: There is good evidence for the efficacy of biological agents in patients with RA. Safety data confirm an increased risk of bacterial infection and TB with TNFi compared with conventional DMARDs.